Induction of gut leakage in young broiler chickens fed a diet with low rye inclusion. Issue 12 (December 2021) - Santos, Regiane R.; Ooosterveer-van der Doelen, Marjolein A.M.; Tersteeg-Zijderveld, Monique H.G.; Molist, Francesc; Gehring, Ronette
Abstract: The aim of the present study was to assess the absence of a non-starch polysaccharide (NSP) enzyme in a broiler diet containing a low level (10%) of rye inclusion. Two experimental groups with 40 Ross broilers each, were fed a diet containing 10% rye. One group was supplemented with a NSP enzyme, and the other was not supplemented with the enzyme to increase intestinal viscosity. The birds were fed the respective diets for 14 or 28 days. Intestinal sections were submitted to morphological, morphometric and mRNA-level gene expression analyses. To assess gut leakage, 150 min before euthanasia, broilers had no access to feed and received an oral gavage with fluorescein isothiocyanate-labelled dextran (FITC-d). Serum levels of FITC-d, D-lactate, tight-junction-associated protein 1 (TJAP1), citrulline and ovotransferrin were determined. A significant increase in FITC-d levels was observed in the 14-day-old birds fed the non-supplemented rye diet, and no other serum markers were affected. These birds presented a decreased villus height/crypt depth (VH:CD) ratio and an increased degree of damage in the jejunum. The ileum VH:CD increased, and the goblet cell number decreased in 28-day-old birds fed the non-supplemented rye diet. When broilers were fed the non-supplemented rye diet, the mRNA expression of the tight-junction zona occludens 1 (ZO1) was significantly decreased in the jejunum of 14-day-old broilers, whereas a significant decrease in jejunum mRNA expression of ZO2 and mucin-2 (MUC2) was observed in the jejunum of 28-day-old broilers. In contrast, a significant increase in the mRNA expression of ZO2 was observed in the ileum from 28-day-old broilers fed the non-supplemented rye diet. In conclusion, a 10% rye diet causes intestinal stress in young broiler chickens when the feed is not supplemented with a NSP enzyme. This study may be applied as experimental model of mild gut leakage of broiler chickens. Abstract : Intestinal permeability, Dietary challenge, Gene expression, Histology, Serum.